2017
DOI: 10.21608/ijhth.2017.30192
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Work- Life Balance and Employee Engagement among Flight Attendants

Abstract: Work-life balance and employee engagement have become two considerable concepts that capture the attention of both academics and practitioners. The prime concern of this paper is to examine the relationship between work-life balance and employee engagement among flight attendants in Egypt. The study focuses on the positive side of work life balance (work life polices and supervisor support) and how they sustain employee engagement. Primary data was conducted using a questionnaire survey of flight attendants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Flextime refers to a flexible work arrangement that allows employees to have control over their work schedules, particularly in terms of the start and end times of their workday (Crowley & Kolenikov, 2014;White et al, 2020). It provides employees with the flexibility to adjust their working hours to accommodate personal needs, such as family responsibilities, personal appointments, or other commitments (Chapman et al, 2016;Mohamed & Zaki, 2017).…”
Section: Flextimementioning
confidence: 99%
“…Flextime refers to a flexible work arrangement that allows employees to have control over their work schedules, particularly in terms of the start and end times of their workday (Crowley & Kolenikov, 2014;White et al, 2020). It provides employees with the flexibility to adjust their working hours to accommodate personal needs, such as family responsibilities, personal appointments, or other commitments (Chapman et al, 2016;Mohamed & Zaki, 2017).…”
Section: Flextimementioning
confidence: 99%
“…Consistent with previous studies (Yanıkoğlu et al, 2020), this study also found that the biggest challenge for female pilots is how to balance work and family. It is recommended that airlines pay attention to the concerns of female pilots and formulate family-friendly policies to help female pilots maintain a work-family balance (Mohamed & Zaki, 2017), such as designing flexible scheduling systems that allow female pilots to arrange their own flights or allow female pilots to apply for same-day round-trip schedules to take into account the needs of family life.…”
Section: Work-life Balancementioning
confidence: 99%
“…Meanwhile [21] defined WLB as companies providing support for the employees, allowing work flexibility, and granting personal leave quickly; the company's top managers usually decide matters. [22] described that past studies revealed WLB contributes to business success and creates a competitive advantage for companies. The airline industry is a sensitive service industry.…”
Section: Introductionmentioning
confidence: 99%